Root pH variation of herbaceous plants among plant functional groups in response to climate and soil gradients on the Tibetan alpine grasslands - Lirong Zhao; Bo Pang; Jiangtao Hong; Xingxing Ma; Ziyin Du; Xiaodan Wang (Ecology and Evolution)
Abstract Plant pH is an emerging functional trait that plays important roles in physiological processes and nutrient cycling. However, how root pH varies among plant functional groups (PFGs) and the regulatory factors on a large scale remain unclear. Therefore, we quantified root pH variation of herbaceous plants in four PFGs from 20 sites on the Tibetan Plateau along a 1600 km transect and explored the correlations between root pH and different PFGs, climate and soil conditions. The results showed that the root pH of herbaceous plants was slightly acidic (6.46 ± 0.05). Grasses had the highest root pH (6.91 ± 0.10) across all functional groups (p < .05), whereas legumes had the lowest (5.90 ± 0.08; p < .05). The root pH decreased with mean annual precipitation, aridity index, soil water content and soil stress coefficient, whereas the significant positive correlation with soil pH. PFGs, climate and soil explained 5.39, 11.15 and 24.94% of the root pH variance, respectively. This study provided a comprehensive analysis of root pH patterns in herbaceous plants over a large spatial scale. Root pH was controlled by the combined influence of PFGs, climate and soil properties, with moisture status being the main influential factor. In contrast to the leaf pH, the root pH of herbaceous plants is strongly affected by the soil pH along environmental gradients. Our findings provide new insights into root functional traits and survival strategies of herbaceous plants in alpine ecosystems.